Theoretical computation of the electrocatalytic performance of CO2 reduction and hydrogen evolution reactions on graphdiyne monolayer supported precise number of copper atoms. (27th January 2021) - Feng, Zhen; Tang, Yanan; Ma, Yaqiang; Li, Yi; Dai, Yawei; Chen, Weiguang; Su, Guang; Song, Zhiying; Dai, Xianqi
Abstract: CO2 reduction (CO2 RR) and hydrogen evolution reactions (HER) are widely used in advanced energy conversion systems, which are urgently required low-cost and high efficient electrocatalysts to overcome the sluggish reaction kinetic and ultralow selectivity. Here, the single-, double-, and triple-atomic Cu embedded graphdiyne (Cu1-3 @GDY) complexes have been systematically modeled by first-principles computations to evaluate the corresponding electric structures and catalytic performance. The results revealed that these Cu1-3 @GDY monolayers possess high thermal stability by forming the firm Cu–C bonds. The Cu1-3 @GDY complexes exhibit good electrical conductivity, which could promote the charge transfer in the electroreduction process. The electronic and magnetic interactions between key species (∗H, ∗COOH, and ∗OCHO) and Cu1-3 @GDY complexes are responsible for the different catalytic performance of HER and CO2 RR on different Cu1-3 @GDY sheets. The Cu2 @GDY complex could efficiently convert CO2 to CH4 with a rather low limiting potential of −0.42 V due to the spin magnetism of catalysts. The Cu1 @GDY and Cu3 @GDY exhibit excellent HER catalytic performance, and their limiting potentials are −0.18 and −0.02 V, respectively. Our findings not only provide a valuable avenue for the design of atomic metal catalysts toward various catalytic reactions but also highlight an important role of spin magnetism in electrocatalysts. Graphical abstract: Image 1 Highlights: The CO2 RR and HER on precise number of copper atoms is systematically investigated. The Cu1-3 @GDY exhibit high thermal stability and good electrical conductivity. The Cu2 @GDY processes a low limiting potential of −0.42 V for CO2 RR. Magnetic interactions between Cu2 @GDY and intermediates boost catalytic ability.